Macroeconomics meets Hyman P. Minsky: the financial theory of investment - L. Randall Wray; Éric Tymoigne (Levy Economics Institute of Bard College, 2008)
In this paper we present a theory of the financing of investment in a modern capitalist economy, following the approach developed by Hyman P. Minsky. We argue that the current financial crisis that began with the collapse of the subprime mortgage market in the United States in 2007 provides a compelling reason to show how his approach offers us a grounding in the workings of financial capitalism. Even if the spreading global financial crisis is successfully contained this time around, it is likely that analyses will incorporate a substantial dose of Minsky's ideas for many years to come. What we present is an alternative to the standard approach that was developed beginning in the early 1970s, based on the efficient markets hypothesis that relegates money and finance to the sidelines. Minsky vehemently denied the relevance of such a theory, at least for a modern capitalist economy with complex, expensive, and long-lived capital assets. In our kind of economy, the method used to finance positions in assets is of critical importance, both for theory and for real-world outcomes. In the first section we present the investment theory of the business cycle developed by John Maynard Keynes, and then examine Minsky's extension that added a financial theory of investment. This allowed Minsky to analyze the evolution, over time, of the modern capitalist economy toward fragilitywhat is well known as Minsky's financial instability hypothesis. In the subsequent section, we update Minsky's approach to finance with a more detailed examination of asset pricing and of the evolution of the banking sector. In the final section we briefly review the insights that such an approach can provide for analysis of the current global financial crisis.
Keywords: E12; E22; E32; E44; G11; G12; 330; Hyman P. Minsky; John Maynard Keynes; financial instability hypothesis; debt deflation; investment finance; asset prices